Surface structure and electronic properties of carbon supported PdAu nanoparticles and their catalytic behavior toward the oxygen reduction reaction - Gallo, Irã Borges Coutinho (2018)
Carbon supported PdAu nanoparticles with different Au contents (20-50% in atoms) were synthesized using a procedure carried out in a liquid two-phase system. As-prepared materials presented similar average particle diameter (~3nm) with narrow distribution over the carbon support, as shown by Transmission Electronic Microscopy (TEM). The combined data from X-ray Diffraction (XRD) and X-ray Photoelectron Spectroscopy (XPS) suggest that nanoparticles had Pd-enriched surfaces and Au-rich interiors. Cyclic Voltammetry (CVs) studies in H2SO4 further reinforced these findings, confirming that the nanoparticle surfaces were enriched with Pd. Moreover, XPS results show that increasing the Au content of PdAu alloys leads to varying amounts of surface-like and bulk-like Pd oxide, with a significant increase of metallic Pd. This result is consistent with data of X-ray Absorption Spectroscopy (XAS) around Pd L3 edge, which revealed that Au promotes an increase in the electronic occupancy of the Pd 4d band. Therefore, this whole set of characterizations suggests that the presence of Au in PdAu nanoalloys decreases the Pd affinity for oxygen, giving Pd a more noble-like character. In addition, the influence of ligand and ensemble effects on electrochemical surface processes, such as oxide formation/reduction, CO oxidation and hydrogen adsorption were also investigated. This was also a necessary step in order to determine the best technique to measure the Electrochemical Active Area (EAA) of Pd. The, electrocatalytic activity toward the Oxygen Reduction Reaction (ORR) was evaluated using a rotating ring-disk electrode in O2 saturated H2SO4 and KOH solutions. On acidic medium, increasing the Au content on PdAu nanoparticles lead to a consistent decrease in catalyst performance and a considerable increase in H2O2 production, suggesting a 2-electron pathway for the ORR. In contrast, on alkaline solution the PdAu 50:50 presented by far the best catalytic activity and the lowest production of H2O2, suggesting a 4-electron pathway for the ORR. Accelerated stability tests were also performed in both electrolytes. On acidic medium, the presence of Au seems to increase the rate of Pd dissolution. That was also observed in alkaline medium. In summary, in acidic medium, as ORR catalysts, PdAu nanoparticles were overall worse than pure Pd. However, in alkaline medium, the PdAu materials were not only better catalyst than pure Pd, but also the PdAu 50:50 surpassed Pt, proving to be a promising catalyst for use in alkaline fuel cells.